Measuring the refractive index of a methanol - water mixture according to the wavelength - Nguyen, Dung Tien; Trung, Le Canh; Cuong, Nguyen Duy; Quang, Ho Dinh; Khoa, Dinh Xuan; Phu, Nguyen Van; Lanh, Chu Van; Vinh, Nguyen Thanh; Thuy, Do Thanh; Thuan, Bui Dinh (Photonics Letters of Poland, 2021)
The refractive index of the methanol-water mixture depending on the wavelength at different concentrations was determined by our experimental method using a Michelson interferometer system. A comparative study of Gladstone-Dale, Arago–Biot and Newton relations for predicting the refractive index of a liquid has been carried out to test their validity for the methanol-water mixture with the different concentrations 30%, 40%, 50%, 60%, 80%, and 100%. The comparison shows the good agreement between our experimental results and the results in the expressions studied over the wavelength range approximately from 450 to 850 nm. Full Text: PDF References S. Sharma, P.B. Patel, R.S. Patel, "Density and Comparative Refractive Index Study on Mixing Properties of Binary Liquid Mixtures of Eucalyptol with Hydrocarbons at 303.15, 308.15 and 313.15 K", E-Journal of Chemistry 4(3), 343 (2007). CrossRef A. Gayathri, T. Venugopal, R. Padmanaban, K. Venkatramanan, R. Vijayalakshmi, "A comparative study of experimental and theoretical refractive index of binary liquid mixtures using mathematical methods", IOP Conf. Series: Materials Science and Engineering 390, 012116 (2018). CrossRef A. Jahan, M.A. Alam, M.A.R. Khan, S. Akhtar, "Refractive Indices for the Binary Mixtures of N, N-Dimethylformamide with 2-Butanol and 2-Pentanol at Temperatures 303.15 K, 313.15 K, and 323.15 K", American Journal of Physical Chemistry 7(4), 55 (2018). CrossRef N. An, B. Zhuang, M. Li, Y. Lu, Z. Wang, "Combined Theoretical and Experimental Study of Refractive Indices of Water–Acetonitrile–Salt Systems", J. Phys. Chem. B 119(33), 10701 (2015). CrossRef M. Upadhyay, S.U. Lego, "Refractive Index of Acetone-Water mixture at different concentrations", American International Journal of Research in Science, Technology, Engineering & Mathematics 20(1), 77 (2017). CrossRef T.H. Barnes, K.Matsumoto, T. Eiju, K. Matsuda, N. Ooyama, "Grating interferometer with extremely high stability, suitable for measuring small refractive index changes", Appl. Opt. 30, 745 (1991). CrossRef B. W. Grange, W. H. Stevenson, R. Viskanta, "Refractive index of liquid solutions at low temperatures: an accurate measurement", Applied Optics 15(4), 858 (1976). CrossRef P. Hlubina, "White-light spectral interferometry with the uncompensated Michelson interferometer and the group refractive index dispersion in fused silica", Optics Communications 193(1-6), 1 (2001). CrossRef P. Hlubina, W. Urbanczyk, "Dispersion of the group birefringence of a calcite crystal measured by white-light spectral interferometry", Meas. Sci. Technol. 16(6), 1267 (2005). CrossRef P. Hlubina, D. Ciprian, L. Knyblová, "Direct measurement of dispersion of the group refractive indices of quartz crystal by white-light spectral interferometry", Optics Communications 269(1), 8 (2007). CrossRef S. R. Kachiraju, D. A. Gregory, "Determining the refractive index of liquids using a modified Michelson interferometer", Optics & Laser Technology 44(8), 2361 (2012). CrossRef F. Gladstone, D. Dale, "XXXVI. On the influence of temperature on the refraction of light", Philos. Trans. R. Soc. 148, 887 (1858). CrossRef D.F.J. Arago, J.B. Biot, Mem. Acad. Fr. 15, 7 (1806). CrossRef Kurtz S S and Ward A L J, "The refractivity intercept and the specific refraction equation of Newton. I. development of the refractivity intercept and comparison with specific refraction equations", Franklin Inst. 222, 563-592 (1936). CrossRef K. Moutzouris, M. Papamichael, S. C. Betsis, I. Stavrakas, G. Hloupis, D. Triantis, "Refractive, dispersive and thermo-optic properties of twelve organic solvents in the visible and near-infrared", Appl. Phys. B 116, 617 (2013). CrossRef S. Kedenburg, M. Vieweg, T. Gissibl, H. Giessen, "Linear refractive index and absorption measurements of nonlinear optical liquids in the visible and near-infrared spectral region", Opt. Mater. Express 2(11), 1588 (2012). CrossRef